Analisis Adopsi Teknologi Budidaya Karet Berdasarkan Faktor Teknis dan Sosial Ekonomi Petani di Desa Antutan Kabupaten Bulungan (International Forum of Researchers and Lecturers, 2026)
Rubber (Hevea brasiliensis) is an important plantation commodity that contributes to improving rural livelihoods. However, the productivity of smallholder rubber plantations remains relatively low due to various technical constraints, socio-economic conditions, and limited farmers’ knowledge and technology. This study aims to analyze the influence of technical aspects of cultivation and socio-economic aspects on farmers’ knowledge and technology in rubber cultivation in Desa Antutan, Kecamatan Tanjung Palas, Kabupaten Bulungan. This research employed a mixed methods approach with a descriptive design. Quantitative data were collected through questionnaires distributed to 30 rubber farmers selected using purposive sampling, while qualitative data were obtained through in-depth interviews and documentation. Quantitative data were analyzed using multiple linear regression with SPSS software, while qualitative data were analyzed through data reduction, data display, and conclusion drawing The results indicate that technical aspects of cultivation and socio-economic aspects simultaneously influence farmers’ knowledge and technology in rubber cultivation. Partially, technical cultivation aspects have a more dominant effect than socio-economic aspects. Qualitative findings reveal that the main problems faced by farmers include improper tapping techniques, aging rubber trees, rubber price fluctuations, and limited access to agricultural training and extension services.